2016
DOI: 10.1103/physrevb.93.205432
|View full text |Cite
|
Sign up to set email alerts
|

Local density of states and its mesoscopic fluctuations near the transition to a superconducting state in disordered systems

Abstract: We develop a theory of the local density of states (LDOS) of disordered superconductors, employing the non-linear sigma-model formalism and the renormalization-group framework. The theory takes into account the interplay of disorder and interaction couplings in all channels, treating the systems with short-range and Coulomb interactions on equal footing. We explore 2D systems that would be Anderson insulators in the absence of interaction and 2D or 3D systems that undergo Anderson transition in the absence of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 53 publications
(133 reference statements)
5
22
0
Order By: Relevance
“…See also Ref. [52] for a microscopic model describing the effect of superconducting fluctuations close to the SIT and their effects on the DOS.…”
mentioning
confidence: 99%
“…See also Ref. [52] for a microscopic model describing the effect of superconducting fluctuations close to the SIT and their effects on the DOS.…”
mentioning
confidence: 99%
“…In classes AII and CI, for simplicity we ignore the BCS interaction channel [27] in this work (see Refs. [57,58,59,60,61,62] where various effects stemming from the Cooper channel renormalizations were scrutinized).…”
Section: Keldysh Response Theory and Resultsmentioning
confidence: 99%
“…62) from which one can infer the renormalized interaction strength γ R . In a disordered normal metal, this identity holds to all loop orders, meaning the charge compressibility κ defined in Eq.…”
mentioning
confidence: 99%
“…Within plain perturbation theory the average density of states near T c is strongly affected by Cooper channel attraction [64][65][66]. These classical results can be extended to incorporate the renormalization group flow near the non-interacting critical point [42].…”
Section: Pacsmentioning
confidence: 99%
“…It was found that in some range of parameters multifractality favours the superconducting instability which results in enhanced superconducting transition temperature T c in comparison with the clean case. Recently, the present authors have demonstrated that near the superconducting transition with enhanced T c one can expect enhanced mesoscopic fluctuations of the local density of states governed by the critical exponents for the non-interacting critical point [42].…”
Section: Pacsmentioning
confidence: 99%